WORK LIFE BALANCE AND ACADEMIC STRESS EFFECTS ON MANAGEMENT STUDENT BURNOUT MEDIATED BY SELF EFFICACY - Dwi Indah; Heru Baskoro (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study examines the effects of work-life balance and academic stress on burnout among management students, with self-efficacy as a mediating variable. Unlike previous studies that examined these predictors separately, this research integrates them to reveal the complex mediating mechanisms of self-efficacy. Research Methodology: This quantitative study employed a causal survey design involving 203 active management students at Universitas Muhammadiyah Gresik, selected via purposive sampling. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). Results: Academic stress emerged as the strongest predictor of burnout, while work-life balance significantly reduced it. Self-efficacy demonstrated competitive partial mediation with a suppressor effect for both predictors, revealing that its protective role is complex when analyzed simultaneously with correlated predictors rather than acting as a simple unidirectional buffer. Conclusions: Reducing academic burnout requires prioritizing academic stress management and work-life balance enhancement. Self-efficacy interventions alone may be insufficient without addressing underlying stressors and resource imbalances. Limitations: The cross-sectional design and single-institution sample limit generalizability. Structural multicollinearity among predictors requires cautious interpretation of direct path coefficients. Contributions: Theoretically, this study extends Conservation of Resources theory by demonstrating how self-efficacy operates through a complex suppressor mechanism when resource depletion and maintenance factors are analyzed simultaneously. Practically, it guides institutions in developing integrated interventions addressing stress management, work-life balance, and psychological capital